The Time Is Up: Compression of Visual Time Interval Estimations of Bimodal Aperiodic Patterns - Duarte, Fabiola; Lemus, Luis (Frontiers in Integrative Neuroscience, 2017)
The ability to estimate time intervals subserves many of our behaviors and perceptual experiences. However, it is not clear how aperiodic (AP) stimuli affect our perception of time intervals across sensory modalities. To address this question, we evaluated the human capacity to discriminate between two acoustic (A), visual (V) or audiovisual (AV) time intervals of trains of scattered pulses. We first measured the periodicity of those stimuli and then sought for correlations with the accuracy and reaction times (RTs) of the subjects. We found that, for all time intervals tested in our experiment, the visual system consistently perceived AP stimuli as being shorter than the periodic (P) ones. In contrast, such a compression phenomenon was not apparent during auditory trials. Our conclusions are: first, the subjects exposed to P stimuli are more likely to measure their durations accurately. Second, perceptual time compression occurs for AP visual stimuli. Lastly, AV discriminations are determined by A dominance rather than by AV enhancement.